2020
DOI: 10.22454/fammed.2020.147410
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Provider Education on Inappropriate NSAID Prescribing Rates

Abstract: Background and Objectives: Nonsteroidal anti-inflammatory drugs (NSAIDs) are one of the most commonly used pain medications among US adults with about 70 million people regularly taking NSAIDs annually. Despite clear recommendations from current clinical practice guidelines and recent supporting literature, NSAIDs are continually prescribed inappropriately in patients with chronic kidney disease (CKD), hypertension (HTN), and heart failure (HF). The purpose of this project was to determine the impact of direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This finding is congruent with other research that found a decrease in the rate of NSAID use and inappropriate NSAID prescribing after pharmacist intervention. 11,12 While discontinuation rates of oral NSAIDs were notable in our cohort, the number of patients on topical NSAIDs remained the same (23 patients). However, deprescribing of NSAIDs was still successful in this category, as all patients who were originally on diclofenac gel 10% eventually reduced their dose to diclofenac gel 2.32%.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This finding is congruent with other research that found a decrease in the rate of NSAID use and inappropriate NSAID prescribing after pharmacist intervention. 11,12 While discontinuation rates of oral NSAIDs were notable in our cohort, the number of patients on topical NSAIDs remained the same (23 patients). However, deprescribing of NSAIDs was still successful in this category, as all patients who were originally on diclofenac gel 10% eventually reduced their dose to diclofenac gel 2.32%.…”
Section: Discussionmentioning
confidence: 77%
“…The mean (SD) age of patients included was 53 (11) years. The mean (SD) number of medications each patient took was 6.6 (4.5).…”
Section: Resultsmentioning
confidence: 99%
“…These measures have shown to improve the quality of care in CKD (i.e., proper use of ACEIs, ARBs, statins and avoidance of NSAIDs). [15][16][17] Similarly, the importance of following GFR trends and the recognition of proteinuria as a marker of adverse renal and cardiovascular outcomes needs to be disseminated among primary care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Some recommended tackling this issue from the patient's level by "empowering patients to make the right treatment decisions" (13). In the USA, pharmacists gave education to primary care providers on safe NSAID 9 habits in high-risk patient populations and it had a "signi cant impact on minimizing inappropriate prescribing patterns" (17). A study on this same issue done in Thailand recommended that physicians prescribe NSAIDs with the shortest duration and lowest effective dose (18).…”
Section: Introductionmentioning
confidence: 99%
“…The US study suggested having pharmacists do medication reviews to coordinate medical records across clinical settings (17). A study done in Mexico that studied Computerized clinical decision support systems (CCDSS) found that 40% of physicians thought that it would allow them to improve their daily practice as it "solved their doubts and above all it provided them with new options to solve their prescription problems" (20).…”
Section: Introductionmentioning
confidence: 99%